Neural stem cell isolation and culture from C57BL/6 mice - Koirala, S; Shah, S; Khanal, L (Journal of College of Medical Sciences-Nepal, 2015)
INTRODUCTION A widely used in vitro culture, the neurosphere assay (NSA) has provided a means to retrospectively identify neural progenitor cells as well as to determine both their selfrenewal capacity. Objective of study was to isolate and compare growth of the embryonic neuronal stem cell and adult neuronal stem cells in presence of Epidermal Growth Factor (EGF) and Fibroblastic Growth Factor (FGF2). MATERIALS AND METHODS Embryonic neuronal stem cell were collected from cortical plate of dorsal telencephalon of fifteen C57BL/6 transgenic mice using stereoscopic microscope on 11th gestational day (GD). Adult mammalian neuronal stem cells taken from subventricular zone (SVZ) of the lateral ventricles and subgranular layer of the dentate gyrus of the hippocampus were cultured. The growth for the neurosphere was then observed in interval of 24 and 72 hours. RESULT The adult stem cell culture showed few intact cells with high amount of debris and 9% heterogeneous sphere after 24 hours while only 20 % was observed at the end of 72 hours. Higher proliferation rate was observed in embryonic neurospheres than the adult stem cell culture. CONCLUSION Presence of EGF and basic FGF2 is essential for culture of neurospheres. Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 1-3